Effect of Design Thinking Method on Academic Achievement, Creativity and Digital Skills in Science among Middle Stage Students - KAUR, NAVDEEP; RAI, MONKIA (INDIAN EDUCATIONAL REVIEW, 2025)
The current study examines how middle-stage students’ academic achievement, creativity and digital skills in science are affected by the design thinking method. A sample of 100 eighth-grade students from two separate schools were selected by the Simple Random Sampling method; fifty each in the experimental group and control group. The investigator followed the five-step design thinking model of Hasso Plattner–2005 to teach the students, which included Empathy, Define, Ideate, Prototype and Test. A hybrid mode of Learning was followed to conduct the study. In the first three steps (Empathy, Define, Ideate), students deal with the community members through environmental activities and find out the solution to the problem through brainstorming sessions in the last two steps (Prototype and Test), students create the prototype in a digital form based on the provided solution and then teacher provided feedback in an online mode. Miro boards were used by the students to design a project in the prototype stage and then the teacher provided feedback to the students. The pre- and post-tests were analysed statistically using Mean, SD, T-Test and ANOVA to assess students’ academic achievement, creativity and digital skills in science. The results of this study demonstrated a positive and significant difference between students who were taught the Design Thinking technique and those who were taught the conventional way, which helped to develop the student’s creativity, digital skills and learning of science